The historical evolution of the regulations for the Florence Nightingale Medal - Wang Qian; Zhu Rui-Fang; Duan Zhi-Guang (Sciendo, 2018)
This study aimed to explore the 100-year changes in regulations for the Florence Nightingale Medal.